Peran Self Efficacy, Dukungan Sosial dan Optimisme Terhadap Grit pada Anggota Tamtama - Devi Ulfa Sari; Fitri Andriani (PT. PENERBIT TIGA MUTIARA, 2024)
This study aims to examine the effect of self-efficacy, social support, and optimism on grit in TNI-AD Private members who took the regular Secaba (National Military Commission) transfer test. This study used a quantitative method with a correlational research design. The sample used was 50 randomly selected Private members. Data were collected through a questionnaire that measured the three independent variables (self-efficacy, social support, and optimism) and grit as the dependent variable. The results of the multiple linear regression analysis showed a significance value of 0.000, indicating that self-efficacy, social support, and optimism had a significant effect on grit. The results showed that social support made the largest contribution to increasing grit, followed by optimism and self-efficacy. Overall, the three variables contributed 75.4% to the grit level of TNI-AD Private members. This finding provides important insight that the combination of self-confidence, support from the surrounding environment, and an optimistic outlook can increase individual persistence in facing challenges, especially in the Secaba selection.